Tenderness - Godár, Vladimír 1956- (Second Run, 2020)
"A rich and complex coming-of-age story, Tenderness focuses on a passionate and often cruel ménage à trois shaped by a country in the throes of political upheaval and social transformation. Cited as one of the finest ever Slovak feature debuts, the film marked the arrival of Šulik as one of international cinema's most vital talents. Slovak filmmaker Martin Šulík’s striking debut feature focuses on a strange triangular relationship shaped by the unspoken undercurrents of political upheaval and social transformation that surround it. [...]" [secondrundvd.com]
Original: Tschechoslowakei 1991
Special features: presented from a new HD transfer of the 2K restoration of the film, approved by the director ; Hurá (1989) - Martin Šulik's acclaimed short film ; On Tenderness (2020) - a new and exclusive documentary on the film and its legacy, produced by the Slovak Film Institute ; 20-page booklet featuring new writing on the film by author and film historian Peter Hames ; new English translation ; world premiere release on Blu-ray
Bildformat 1.66:1
Keywords: Film; Blu-Ray-Disc